Landscape transformations produce favorable roosting conditions for turkey vultures and black vultures - Jacob E. Hill (Nature Portfolio, 2021)
Abstract Recent increases in turkey vulture (Cathartes aura) and black vulture (Coragyps atratus) populations in North America have been attributed in part to their success adapting to human-modified landscapes. However, the capacity for such landscapes to generate favorable roosting conditions for these species has not been thoroughly investigated. We assessed the role of anthropogenic and natural landscape elements on roosting habitat selection of 11 black and 7 turkey vultures in coastal South Carolina, USA using a GPS satellite transmitter dataset derived from previous research. Our dataset spanned 2006–2012 and contained data from 7916 nights of roosting. Landscape fragmentation, as measured by land cover richness, influenced roosting probability for both species in all seasons, showing either a positive relationship or peaking at intermediate values. Roosting probability of turkey vultures was maximized at intermediate road densities in three of four seasons, and black vultures showed a positive relationship with roads in fall, but no relationship throughout the rest of the year. Roosting probability of both species declined with increasing high density urban cover throughout most of the year. We suggest that landscape transformations lead to favorable roosting conditions for turkey vultures and black vultures, which has likely contributed to their recent proliferations across much of the Western Hemisphere.